Relationship of serum hepatitis B Virus DNA levels with Hepcidin, Pentraxin-3, Zonulin, and Copeptin in chronic hepatitis B patients - Ezer, Burak; Ozdemir, Mehmet (The Journal of Infection in Developing Countries, 2025)
Introduction: This study aims to investigate the serum levels of hepcidin, pentraxin-3 (PTX-3), Zonulin, and Copeptin biomarkers, which can be detected by the more cost-effective and practical ELISA method compared to the quantitatively determined HBV DNA by molecular methods, and to contribute to studies on biomarkers that will facilitate the antiviral treatment management of chronic Hepatitis B patients. Methodology: Serum samples from 105 patients with HBsAg detected for more than 6 months and 35 control group individuals without any liver or chronic disease were included in the study. The serum HBV DNA levels of the patients were determined by the Real Time PCR (Anatolia, Turkey) method. Patients were divided into three different groups based on their HBV DNA levels (IU/mL): 35 patients with levels between 100-102, 35 patients with levels between 103-105, and 35 patients with levels between 106-108. These groups were evaluated as having mild, moderate, and severe viral loads. Results: A statistically significant difference was found in serum hepcidin levels between the control group and the group with severe viral load (p = 0.01). The difference in serum PTX-3 levels between the control group and the other three groups was statistically significant (p < 0.001). A statistically significant difference in Copeptin levels was determined between the group with severe viral load and moderate, mild, control groups (p = 0.007; p = 0.013; p = 0.036). Conclusions: Important clues have been obtained about markers that can give an idea about HBV DNA, but studies on larger populations are needed.